Public Policy for Venture Capital - Christian Keuschnigg; Søren Bo Nielsen (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper proposes a simple partial equilibrium model to investigate the effects of government policy on venture capital backed investments. Giving up an alternative career, entrepreneurs focus their effort on a single, high risk venture each. Venture capitalists acquire an equity stake and offer a base salary as well. In addition to providing incentive compatible equity finance, they support the venture with managerial advice to raise survival chances. We analyze several policy measures addressed at venture capital activity: government spending on entrepreneurial training, subsidies to equipment investment, and output subsidies at the production stage. While these measures stimulate entrepreneurship, only cost-effective government services can improve welfare.
Keywords: 330; Venture capital; moral hazard; managerial advice; public policy